2020
DOI: 10.5194/acp-2020-648
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Source identification of atmospheric organic vapors in two European pine forests: Results from Vocus PTR-TOF observations

Abstract: Abstract. Atmospheric organic vapors play essential roles in the formation of secondary organic aerosol. Source identification of these vapors is thus fundamental to understand their emission sources and chemical evolution in the atmosphere and their further impact on air quality and climate change. In this study, a Vocus proton-transfer-reaction time-of-flight mass spectrometer (PTR-TOF) was deployed in two forested environments, the Landes forest in southern France and the boreal forest in southern Finland, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 83 publications
1
3
0
Order By: Relevance
“…One aromatic oxidation factor (ARO), an alkane/alkene oxidation factor (ALK), two nighttime terpene factors (Night_MT dominated by NO 3 chemistry and MT dominant by O 3 + NO x ), and an NPF-related factor were also distinguished from individual ranges. The results in this study agreed well with previous research on OOM factorization, measured by CI–APi–TOF in foresty or suburban environments. ,,, Note that this good agreement should not be interpreted as indicating that the Orbitrap technology is not advantageous compared to traditional techniques but rather a validation for the results in our study. On the one hand, the Orbitrap reduced significantly the efforts in peak fitting while offering an unprecedented accuracy in the identification of the analytes, which provided the crucial chemical/molecular information needed to understand the atmospheric processes.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…One aromatic oxidation factor (ARO), an alkane/alkene oxidation factor (ALK), two nighttime terpene factors (Night_MT dominated by NO 3 chemistry and MT dominant by O 3 + NO x ), and an NPF-related factor were also distinguished from individual ranges. The results in this study agreed well with previous research on OOM factorization, measured by CI–APi–TOF in foresty or suburban environments. ,,, Note that this good agreement should not be interpreted as indicating that the Orbitrap technology is not advantageous compared to traditional techniques but rather a validation for the results in our study. On the one hand, the Orbitrap reduced significantly the efforts in peak fitting while offering an unprecedented accuracy in the identification of the analytes, which provided the crucial chemical/molecular information needed to understand the atmospheric processes.…”
Section: Resultssupporting
confidence: 91%
“…To our knowledge, only a few studies have been conducted to understand ambient VOC oxidation by PMF analysis, ,,, most of which have substantial influence from biogenic sources. Different from previous studies, anthropogenic-originated contribution in our study was absolutely dominant in the Shanghai urban environment, 94% on average (sum of the factors, excluding Night_MT and MT).…”
Section: Resultsmentioning
confidence: 99%
“…Considering this unusual observation, it was decided to validate -a posteriori -the NO 3 concentration calculation methodology used in the present study, by applying it to other datasets from previous campaigns carried out in a similar environment. Our choice focused on a boreal forested site, at the SMEAR II station, Hyytiälä, southern Finland, with one dataset from the HUMMPA-COPEC-10 campaign, performed in summer 2010 (Yassaa et al, 2012;Hens et al, 2014;Mogensen et al, 2015) and one gathering some ambient measurements monitored in summer 2019 (Li et al, 2020a)). In both cases, NO 3 concentrations were found to be maximum at nighttime, as usually observed.…”
Section: Evolution Of Physico-chemical Parameters and Gaseous Phase C...mentioning
confidence: 99%
“…Forest found the diel profile of MT to be consistent with C10H17O + , with an average evening [C10H16O]:[ΣMT] of 0.03, compared to 0.08 in this study. The authors suggested that C10H16O was partially sourced from directly-emitted camphor or a MT oxidation product (Li et al, 2020(Li et al, , 2021, although at the CNNF site there are few species that directly emit camphor and those that do (north white cedar, white spruce), emit camphor in low amounts . Figure 3 (Atkinson and Arey, 2003).…”
mentioning
confidence: 99%